"Engaging in my rural community": perceptions of people aged 85 years and over. Issue 1 (1st January 2018) - Neville, Stephen; Adams, Jeffery; Napier, Sara; Shannon, Kay; Jackson, Debra
ABSTRACT: Purpose:  Globally, numbers of people aged 85 years and over are increasing. Many older people, including those 85 years and over, are ageing in rural areas. For successful ageing in place, physical and social environments must be appropriate. The aim of this study is to understand the influence the physical and social environments have on enabling those aged 85 years and over to remain engaged in a rural community. Method:  Utilizing an environmental gerontological approach, semi-structured interviews were undertaken with 15 people who lived independently in a rural community. Following transcription data were analyzed and themes identified. Results:  Two themes were identified; "Negotiating the physical environment: 'Getting there and back'" and "Maintaining social networks: 'Places to go, people to see'". The findings provide insight into the importance of driving, parking close to amenities and negotiating the local environment to this group of older people and their ability to engage with their community. All participants agreed social engagement with friends, family or neighbors was important to them. Conclusion:  These findings highlight the interconnection between physical and social environments. An enabling physical environment is essential to support social participation of people aged 85 years and over.